Appendicular adenoma. Histological finding - Lussheimer, Daniel; Ormaechea, Ernesto; Rondán, Mariela; Misa, Carlos; Chiossoni, Marta; Navarrete, Héctor (Cirugía del Uruguay, 1994)
A case of adenoma of the appendix is presented. As regards the case, its low frequency and clinical presentation is analysed, and emphasis is made on simultaneous colonic pathology